(untitled) (Al-Qamar, 2021)
Nazar-e-Nanak” is a long Poem by Mahdi Nazmi. This poem is a symbol of love and peace. It is written about the life of Baba Guru Nanak Singh, the founder of Sikhism. He was born in Nanak on 15 April 1469-1539), also referred to as Baba Nanak was, the first of the ten Sikh Gurus. His birth is celebrated worldwide as Guru Nanak Gurpurab on Katak Pooranmashi (’full-moon of Kattak’), i.e. October–November. Baba Guru Nanak travelled far and wide across Asia teaching people the message of (One God). “A great leader posse a clear vision, is courageous, has integrity, honesty, humility and clear focus. Mahdi Nazmi tries to describe the mission of a great leader because Great leaders help to people reach their goals, are not afraid to hire people that might be better than them and take pride in the accomplishments.